Ethiopian women's tokophobia of childbirth and its predictors: a systematic review and meta-analysis - Assimamaw, Nega Tezera; Gonete, Almaz Tefera; Angaw, Dessie Abebaw; Techane, Masresha Asmare; Kelkay, Mengistu Mekonnen; Terefe, Bewuketu (Frontiers in Global Women's Health, 2024)
Background: Fear of childbirth is recognized as a growing problem in developing countries, including Ethiopia. The impact of this fear on women's reproductive choices and decisions is significant. Therefore, the systematic review and meta-analysis will help to consolidate the existing research on childbirth-related fear in Ethiopia. Synthesizing the findings and providing a pooled prevalence estimate, can contribute to a better understanding of the scale of the problem in the country.Objective: this systematic review and meta-analysis assessed the pooled prevalence of childbirthrelated fear and its associated factors among pregnant mothers in Ethiopia.Methods: PubMed, Google Scholar, and African Journals Online were searched for included articles. A weighted inverse-variance random-effects model was used to estimate the prevalence of childbirth-related fear. Variations in the pooled estimates of the prevalence were adjusted through subgroup analysis according to the specific region where the study was conducted.Funnel plot and Egger"s regression test were used to check for publication bias. STATA version 14 statistical software was used for meta-analysis.Results: A total of 2,015 pregnant mothers were included. The combined prevalence of fear of childbirth among pregnant mothers was found to be 21 % (95% CI: 19-22; I 2 =0.00%, P value<0.001). Based on the subgroup analysis, the prevalence of fear of childbirth among pregnant mothers was 24% in SNNPRs, 25% in Oromia, and 11 % in Addis Ababa.The findings of the meta-analysis indicating a high prevalence of fear of childbirth among pregnant mothers in Ethiopia and identifying associated risk factors highlight the importance of addressing this issue within the healthcare system. Integrating prevention-based services for mothers with childbirth fears into the antenatal care model could be a valuable approach to support women and mitigate the impact of fear on their reproductive experiences.